I Can Teach and Run a Business! A Qualitative Exploration of Entrepreneurial Behavior among Preservice Economics Teachers - Solikah, Maratus; Narmaditya, Bagus Shandy; Sahid, Sheerad (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2025)
Entrepreneurial readiness among prospective economics teachers has become an urgent issue in teacher education. This study aims to understand the factors that influence entrepreneurial behavior among prospective economics teachers. Using a qualitative approach with a phenomenological method, this study explores the subjective experiences of preservice teacher in an educational university in Malang of Indonesia. Data were collected through in-depth interviews, observations, and documentation of ten informants. The results indicate that the determination of entrepreneurial behavior is determined by six main aspects, including: (1) psychological and cognitive (self-confidence, motivation, and risk taking), (2) social and cultural (norms and social capital), (3) economic (access and financial conditions), (4) education and knowledge (entrepreneurship courses, financial security, and practical experience), and (5) independence and (6) perseverance. Capturing from the Theory of Planned Behavior and Behavioral Economics Theory, this study shows that the entrepreneurial intentions of prospective teachers are influenced by psychological and social aspects. This study provides a conceptual contribution to the development of entrepreneurship education in the teaching environment.